Urea Split Application to Maize (Zea mays L.) Growth Stages of Medium Maturities, Influenced on Grain Yield and Parameter for Yield at Bako, East Wollega, Ethiopia - Megersa Debele; Belay Taressa (International Journal of Agronomy)
Appropriate timing of application can improve crop nutrient consumption efficiency. Maize production is still significantly below than its potential output, even though it is comparatively better than other main cereal crops. One of the main abiotic variables affecting crop growth is the timing of urea split application. Due to these gaps, an experiment was carried out at the Bako Agricultural Research Center during the 2019 and 2020 cropping seasons in order to ascertain the best time to apply urea split in order to maximize the yield and yield attributes of the maize varieties BH-546 and BH-547 in a study area and in countries with comparable agroecologies. Six levels of urea split application time (T1, T2, T3, T4, T5, and T6) were arranged in factorial combinations with two levels of maize varieties. In addition, a randomized complete block design with three replications was used for the previously advised urea split application. The harvest index of maize, grain yield, number of kernels per ear, ear dimension, and number of ears per plant all significantly differed depending on when nitrogen split administration occurred. Mean dry biomass, cob diameter, cob length, cob weight, and thousands seed weight of maize were all highly impacted by the interaction varietals and split time of nitrogen treatment. Compared to the previously recommended (1/2 dose at planting and 1/2 dose at knee height stage of maize), the time of N split application resulted in a significantly higher grain yield (9003.88 kg·ha−1): 1/4 dose at planting + 1/2 dose of N at knee height + 1/4 dose at tasseling of maize. However, three urea application regimes 1/4 dosage at planting time, 1/2 dose at knee height, and 1/4 dose of split application should be utilized in the event of irregular and intensely rainy seasons in order to maximize grain output and yield attributable.